'Cendekia Bitara' award night, honouring contributions of UMP researchers and lecturers - Noor Syahidah, Sabran (Penerbit UMP, 2014)
Universiti Malaysia Pahang (UMP) held its annual 'Cendekia Bitara' Award Night at Zenith Hotel in Kuantan, last May.